(untitled) (Asian Journal of Agriculture, 2018)
Abstract. Setiyoningrum F, Pribadi G, Afiati F, Herlina N, Solikhin A, Lisani N. 2018. Functional properties of Saccharomyces kluyveri Y97-fermented solo black garlic. Asian J Agric 2: 48-51. Saccharomyces kluyveri Y97-fermented solo black garlic was made by fermentation of fresh solo garlic in medium containing S. kluyveri aging in 70°C and relative humidity close to 60%. The fermentation period of fresh solo garlic in the medium was 0, 2, 4 and 6 days. The black aging period was 0 (fresh garlic), 7, 14 and 21 days. Antioxidant capacity, flavonoid content, and total polyphenol were observed. S. kluyveri Y97-fermented solo black garlic had higher antioxidant capacity, flavonoid content and total polyphenol compared to solo black garlic without fermentation. Fermentation of fresh solo garlic by S. kluyveri Y97 before the aging process could increase solo black garlic’s functional properties.